National Earth Observation Program for Digital Earth - the Malaysian Case: Issues in Consideration (Journal of Science, Technology and Innovation Policy, 2021)
Digital Earth, a virtual geospatial data infrastructure, has become a strategic asset to Malaysia in embracing the new economy. Earth Observation Satellite (EOS) is currently a major tool employed to build and maintain DE. Acknowledging the strategic need of having her own capability, Malaysia has embarked into EOS development programs since the early 1990s, starting with TiungSAT-1, a micro-satellite carrying a small camera, followed by RazakSAT, a small satellite carrying a 2.5 m PAN medium-aperture-camera. The current satellite development program, the RazakSAT-2, plans to carry a 1.0m high resolution PAN camera and a 4.0m MS camera, would become a strategic initiative by the Government in developing and accelerating the nation’s capability in the area of satellite technology, and its applications. This paper aims to review the implementation of a national DE, and to discuss the country’s space sector development in support of the DE implementations via the proposed National Space Policy. Emphasis is placed on the EOS program, as described in the policy paper, as well as on supporting local space industry. The paper concludes with identifying several related issues of importance, their impact, and finally, proposes techniques to address these issues.
Keywords: Digital earth Malaysia, National Earth Observation Program